Women's Empowerment in Agriculture Index (WEAI) Pilot II for Bangladesh - International Food Policy Research Institute; Data Analysis and Technical Assistance (International Food Policy Research Institute, 2015)
The Women’s Empowerment in Agriculture Index (WEAI) is a composite measurement tool that indicates women’s control over critical parts of their lives in the household, community, and economy. It allows us to identify women who are disempowered and understand how to increase autonomy and decisionmaking in key domains. The WEAI is also a useful tool for tracking progress toward gender equality, which is one of the Millennium Development Goals. The WEAI measures the empowerment, agency, and inclusion of women in the agriculture sector in an effort to identify ways to overcome those obstacles and constraints. The Index is a significant innovation in its field and aims to increase understanding of the connections between women’s empowerment, food security, and agricultural growth. The Uganda pilot covered five spatially dispersed rural districts in the northern region (Amuru and Kole), central region (Luwero and Masaka), and eastern region (Iganga). The second pilot was conducted to develop and test a revised version of WEAI in the same districts as the original pilot. Sample villages were randomly assigned to receive either the original (1.1) or revised (2.0) versions of the questionnaire.